Harmonic Reduction in Single Boost Converter Fed DC Motor with EMI Input Filter - A. Sivakumar; T. Muthamizhan (Institute of Advanced Engineering and Science, 2018)
DC motor drive system supplied by AC/DC rectifier topology considered as a nonlinear load. It produces harmonic distortions and EMI noise effects in the power systems. In this paper deals with the reduction of supply current harmonics and EMI noise generated by the power electronics converter in the DC motor drive using FFT analysis. The single boost converter along with EMI input filter is proposed in this system to investigate the harmonic reduction in the DC motor drive. The single boost converter fed DC motor drive is modeled and simulated using MATLAB/Simulink software. The simulation results show better agreement with the proposed system.